Study components of Vietnamese cobra venom Naja kaouthia - Thanh, Nguyen Hong; Tan, Nguyen Kim; Hai, Truong Nam; Anh, Hoang Ngoc (Academia Journal of Biology, 2012)
The cobra snakes are distributed in many regions of Vietnam. They contain three species: Naja atra snakes are distributed in the North of Vietnam; Naja sumatra snakes are distributed in the central part of Vietnam and in the east of Cochin; Naja kaouthia snakes are distributed in the west of Cochin. Among these cobra snakes the N. kaouthia are most dangerous snakes for people in the Cochin. The α-neurotoxins, muscarinic toxins and cytotoxins were isolated from snake venoms of Asian N. kaouthia. The compositions of snake venoms depend on their geographic distribution. Until now the compositions of Vietnamese N. kaouthia snake venom were not studied, so we carried out this work. Venom was collected from N. kaouthia snakes breeding in the snake camp in Dong Tam, Tien Giang. Our analysis of N. kaouthia snake venom showed the method RP-HPLC on a Supelcosil C18 column is better than method FPLC on a Sephacryl S-100 for this aim. By method RP-HPLC on a Supelcosil C18 column the N. kaouthia snake venom separed into eight fractions. Toxicity assay on mice showed that six from isolated fractions are toxic (fractions: 1, 2, 3, 4, 5 and 7). The method electrophoresis was used to study protein compositions of isolated fractions and it showed that the toxic fractions 1, 2, 3 have molecular mass in the range of 13-14 kDa, that similar to those of phospholipase. In this time the most toxic fractions 4 and 5 have molecular mass in the range of 6-8 kDa, that similar to neurotoxins isolated from Thai cobra N. kaothia. These fractions will be used for further isolation of neurotoxins. Study anti-bacterium and anti-fungus activities of isolated fractions showed they have no these activities. This result showed the compositions of N. kaouthia snake venom distributed in the South of Vietnam were very different from the compositions of N. atra snake venom distributed in the North of Vietnam. The compositions of N. atra snake venom have anti-bacterium and anti-fungus activities.